Understanding of Deaf Students Using Interactive Media of the BISINDO Sign Speaking Song (Merakit-Yura Yunita) in Online Learning - Shintia Dwi Alika; Amalia Beladinna Arifa; Asti Dwi Sripamuji; Julian Saputra; Risa Riski Amalia; Imada Ramadhanti (Jurnal Paedagogy, 2023)
This research aims to analyze the understanding of deaf students using the interactive media of the BISINDO sign-speaking song (Merakit-Yura Yunita) in online learning. The method used in this research was qualitative method. The subjects of this research were deaf students in SLB Yakut B Purwokerto. The research instrument used observation and questionnaires. Data analysis used interactive analysis, which includes data reduction, data presentation, and drawing conclusions. The results of the research showed that the use of the interactive media of the BISINDO sign language song (Merakit-Yura Yunita) could be applied to online learning for deaf students at the school. Deaf students could gain an understanding of the content contained in this song. In addition, this media is expected to be an innovation in the online learning of deaf students.